2018
DOI: 10.1016/j.nut.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous lipid emulsions and liver function in adult chronic intestinal failure patients: results from a randomized clinical trial

Abstract: All four ILEs tested may be safe even during long-term parenteral nutrition. OO/LCT may be more effective than the others, but more studies in the field are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…There was no significant difference in the amount of lipid delivered to patients across the four cohorts. At the end of 12 months of PN therapy, there was no significant difference in LFTs between the groups; however, at day zero of PN therapy, those who started the soybean/fish oil hybrid had significantly higher serum bilirubin levels, with a significant difference in baseline vs twelve month serum bilirubin …”
Section: Managementmentioning
confidence: 86%
“…There was no significant difference in the amount of lipid delivered to patients across the four cohorts. At the end of 12 months of PN therapy, there was no significant difference in LFTs between the groups; however, at day zero of PN therapy, those who started the soybean/fish oil hybrid had significantly higher serum bilirubin levels, with a significant difference in baseline vs twelve month serum bilirubin …”
Section: Managementmentioning
confidence: 86%
“…Just one of them studied an n-3 PUFA-containing ILE [26]. In this study in 73 patients lower values of total bilirubin, alanine transaminase (ALT) and aspartate transaminase (AST) were detected after 4 weeks [27]. They showed that all four ILEs were safe and had comparable influence on liver function with a slightly better effect from OO/LCT, however recognizing some limitations in interpretation given disparate initial patient characteristics.…”
Section: Intravenous Lipid Emulsions and Liver Functionmentioning
confidence: 90%
“…The authors noted that there was a slight increase in alanine transaminase (ALT), aspartate transaminase (AST), and total bilirubin in the SO ILE group, whereas the MO ILE group experienced a significant decline in all 3 of these parameters. In a follow‐up study, Klek et al randomized 88 CIF patients to 1 of 4 available ILEs (MCT/SO, OO/SO, MO, and SO), and patients were followed up for over a year . At the time of analysis, 23 patients were lost to follow‐up (4 in MCT/SO, 5 in OO/SO, 6 in MO, and 8 in SO ILE groups).…”
Section: Clinical Datamentioning
confidence: 99%
“…In a follow-up study, Klek et al randomized 88 CIF patients to 1 of 4 available ILEs (MCT/SO, OO/SO, MO, and SO), and patients were followed up for over a year. 38 At the time of analysis, 23 patients were lost to follow-up (4 in MCT/SO, 5 in OO/SO, 6 in MO, and 8 in SO ILE groups). With long-term follow-up, they noted that liver function tests tended to stabilize and improve in all 4 groups, with no significant differences.…”
Section: Clinical Datamentioning
confidence: 99%